2018
DOI: 10.3847/1538-4357/aaccea
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Archeology with the AEGIS Survey: The Evolution of Carbon and Iron in the Galactic Halo

Abstract: Understanding the evolution of carbon and iron in the Milky Way's halo is of importance because these two elements play crucial roles in constraining star formation, Galactic assembly, and chemical evolution in the early universe. Here we explore the spatial distributions of the carbonicity, [C/Fe], and metallicity, [Fe/H], of the halo system based on medium-resolution (R∼1300) spectroscopy of ∼58,000 stars in the southern hemisphere from the AAOmega Evolution of Galactic Structure (AEGIS) survey. The AEGIS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 133 publications
9
73
1
1
Order By: Relevance
“…The p-values for V Φ and eccentricity (e) are derived by the K-S two sample test on the distributions of V Φ and eccentricity (e) of the CEMP-s and CEMP-no star samples. We also note that the [C/Fe] value of the CEMPno stars is somewhat lower than that of the CEMP-s stars for all three regions we considered, implying that the mechanism responsible for producing the CEMP-s stars produces more carbon at a given metallicity than that responsible for the CEMP-no stars, as revealed in several previous studies (e.g., Yong et al 2013;Spite et al 2013;Bonifacio et al 2015;Hansen et al 2016a,b;Yoon et al 2016Yoon et al , 2018.…”
Section: Spatial Distribution Of Cemp-s and Cemp-nosupporting
confidence: 74%
See 2 more Smart Citations
“…The p-values for V Φ and eccentricity (e) are derived by the K-S two sample test on the distributions of V Φ and eccentricity (e) of the CEMP-s and CEMP-no star samples. We also note that the [C/Fe] value of the CEMPno stars is somewhat lower than that of the CEMP-s stars for all three regions we considered, implying that the mechanism responsible for producing the CEMP-s stars produces more carbon at a given metallicity than that responsible for the CEMP-no stars, as revealed in several previous studies (e.g., Yong et al 2013;Spite et al 2013;Bonifacio et al 2015;Hansen et al 2016a,b;Yoon et al 2016Yoon et al , 2018.…”
Section: Spatial Distribution Of Cemp-s and Cemp-nosupporting
confidence: 74%
“…After dividing CEMP stars into likely membership in the IHP and OHP by consideration of their orbital energies, they calculated the fraction of CEMPno and CEMP-s stars in each halo population, finding that the fraction of CEMP-no stars in the OHP is higher, by about a factor of two, than for CEMP-s stars, while almost equal fractions of CEMP-s and CEMP-no stars were found in the IHP. Yoon et al (2018) also reported similar fractions of the CEMP-no stars in the IHP and OHP, using subgiant and giant stars from the AEGIS survey. They classified the CEMP stars into the CEMPs and CEMP-no stars by A(C), as adopted in this study.…”
Section: Spatial and Kinematic Properties Of Cemp-s And Cemp-no Starsmentioning
confidence: 64%
See 1 more Smart Citation
“…The CEMP-stars are dominant at the lowest metallicities (e.g. Placco et al 2014;Yoon et al 2018). Consequently, we have investigated the [C/Fe] values for the stars with abundances [Fe/H] f itter < -3.0 dex.…”
Section: Carbon Abundance Estimatesmentioning
confidence: 99%
“…13 indicates that there may be a minor bias towards that inclusion of lower metallicity stars in the sample, but accounting for it would only reduce the number of more metal-poor stars relative to the number at [Fe/H] f itter = -3.0 dex. It is also necessary to keep in mind that the observed sample is likely a mixture of both inner and outer halo populations (Carollo et al 2007(Carollo et al , 2010An et al 2013;Yoon et al 2018), which may or may not have similar MDFs for [Fe/H] -3 and below: our sample likely includes stars at Galactocentric distances of up to ∼50 kpc. We intend to perform a full kinematic and spatial analysis of the current sample in a later study.…”
Section: Metallicity Distribution Functionmentioning
confidence: 99%